Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

There are $ \vec{a_1},\vec{a_2},\vec{a_3}, \ldots ,\vec{a_n},\vec{b}\; $ such that $ |\vec{a_i}|>1 $, $ |\vec{b}|<1 $, $ \vec{a_1}+\cdots+\vec{a_n}=0 $ .Prove : $ |\vec{a_1}-\vec{b}|+\cdots+ |\vec{a_n}-\vec{b}| > n $

share|cite|improve this question
Are you talking about...vectors? In the plane? In the space? What have you tried...? – DonAntonio Apr 4 '13 at 2:27
I try $|\overrightarrow{{{a}_{1}}}-\vec{b}|+\cdots +|\overrightarrow{{{a}_{n}}}-\vec{b}|\ge |\overrightarrow{{{a}_{1}}}+\cdots +\overrightarrow{{{a}_{n}}}-n\vec{b}|=|n\vec{b}|>n$,but I use $|\overrightarrow{b}|>1$,not use $|\vec{a_i}|>1$, – geometryscience Apr 4 '13 at 2:42
@DonAntonio, I tried this, that's not enough to get the result. I guess the key is $\sum a_i=0$, but not sure how to use it. And geometryscience's inequality is correct, it is just a generalised version of triangle inequality. – Easy Apr 4 '13 at 3:01
I know it's not enough, @Easy, yet the above inequality that geom. wrote is then enough, without any condition on $\,|a_i|\,$... – DonAntonio Apr 4 '13 at 3:09
The condition given is $|\vec{b}|<1$, not $|\vec{b}|>1$. – pharmine May 13 '13 at 7:24

Lemma. Let $\vec{a}$ be a nonzero vector and $\vec{b}$ be another vector. Then $|\vec{a}-\vec{b}|\ge |\vec{a}|-\vec{b}\cdot\dfrac{\vec{a}}{|\vec{a}|}$.

Proof of Lemma. Use $|\vec{x}||\vec{y}|\ge \vec{x}\cdot\vec{y}$ for $\vec{x}=\vec{a}-\vec{b}$ and $\vec{y}=\dfrac{\vec{a}}{|\vec{a}|}$.

Proof. Using the above lemma, we get \begin{align*} &\sum_{i=1}^n|\vec{a_i}-\vec{b}|\\ &\ge \sum_{i=1}^n \left(|\vec{a_i}|-\vec{b}\cdot\frac{\vec{a_i}}{|\vec{a_i}|}\right)\\ &=\sum_{i=1}^n \left(1-\vec{b}\cdot\vec{a_i}\right)+\sum_{i=1}^n\left(|\vec{a_i}|-1+\vec{b}\cdot\frac{\vec{a_i}}{|\vec{a_i}|}\cdot (|\vec{a_i}|-1)\right)\\ &=n-\vec{b}\cdot\sum_{i=1}^n \vec{a_i}+\sum_{i=1}^n\frac{|\vec{a_i}|-1}{|\vec{a_i}|}(|\vec{a_i}|-\vec{b}\cdot\vec{a_i}). \end{align*}

Here, the second term $\vec{b}\cdot\sum_{i=1}^n \vec{a_i}$ is zero. The third term is positive because $|a_i|>1$ and $$|\vec{a_i}|>|\vec{b}||\vec{a_i}|\ge \vec{b}\cdot\vec{a_i}.$$ The first inequality follows from $|b|<1$. Hence $$\sum_{i=1}^n|\vec{a_i}-\vec{b}|>n.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.